Pregnancy Wastage Due to Fetal Congenital Malformations - Vijayata Sangwan; Shivani Khandelwal; Rajiv Mahendru; Pinkey Lakra; Sunita Siwach (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVES: To study the pattern of various congenital anomalies in rural Haryana. STUDY DESIGN: This was a retrospective study conducted over 1 and ½ years (from January 2015 to June 2016) in a tertiary care center in Haryana, India.